Dielectric properties and electrical conductivity of Ternary Zinc Magnesium Phosphate Glass-derived hydrogel / \c Nor Asfaliza bt Abdullah. - Nor Asfaliza Abdullah (School of Electrical Systems Engineering, Universiti Malaysia Perlis, 2015)
The main research objectives of this project are to fabricate ternary zinc magnesium phosphate glass-derived hydrogel with different magnesium oxide and water content; to analyze the effect of magnesium oxide and water content on the physical properties and structural changes of ternary zinc magnesium phosphate glass of solid glasses and glass-derived hydrogel forms; to analyze the effect of magnesium oxide and water content on the dielectric properties and electrical conductivity of ternary zinc magnesium phosphate glass-derived hydrogel; and to investigate the capacitive behaviour and charge-discharge performance of ternary zinc magnesium phosphate glass-derived hydrogel with different magnesium oxide and water content.